Efficacy of Plantar Glabrous Skin Grafts for Release of Post Burn Contractures of Hand (Medical Forum Monthly, 2024)
Objective: This study examines the efficacy of plantar glabrous skin grafts for treating hand and finger contractures resulting from burns.Study Design: A cross-sectional analysis study.Place and Duration of Study: This study was conducted at the Department of Plastic Surgery & Burns Unit at Khyber Teaching Hospital in Peshawar, Pakistan from January 2022 to January 2023.Methods: Seventy patients aged five to seventy years diagnosed with post-burn palmar contractures were included. hairless glabrous skin harvested from plantar surfaces was used to cover defects after contraction release.Results: Among patients, twenty-six (37.14%) had both palmar and finger contractures, twelve (17.14%) only had finger contractures , and thirty-two (45.71%) solely had palmar contractures . The skin grafts were harvested using a dermatome set between 20–26/1000 of an inch. Dressings were changed six days post-procedure, and patients were followed for ninety days. Successful graft uptake was observed in sixty-six (94.29%) patients. Functional outcomes, assessed via the Vancouver Scar Scale, were rated as good in twenty-three (32.86%) cases, adequate in thirteen (18.57%) cases, poor in four (5.71%) cases, and exceptional in thirty (42.86%) cases.Conclusion: Hairless skin grafts not only demonstrate high survival rates comparable to full-thickness skin grafts but also offer superior aesthetic outcomes in treating burn-induced palmar and finger contractures